Adulteration: Supply of Raw Milk and Prevalence of Adulterated / Prepared Milk : Adulteration of Milk - Ibrahim, Tanveer; Wattoo, Feroza Hamid; Sarwar Wattoo, Muhammad Hamid; Mustafa, Ghulam (Pakistan Journal of Health Sciences, 2023)
Raw milk adulteration is one of the food fraud to gain financial benefits by removing fat and cream from whole milk and compensating it by addition of different adulterants to make it near to wholesome milk. Objectives: To analyze milk adulterants to not only describe about the prevalence of different milk adulterants but also confirm the sources of adulterants being used for the synthesis of semi synthetic or prepared milk due to their characteristics which they impart to form a sort of wholesome milk. Methods: In this regard total of 190 raw milk samples from cow and buffalo sources along with control and in house standards were taken to detect most prevailing adulterants in raw milk samples through automated and/or titration based manual recommended methods. Results: The analysis of different adulterants in milk samples showed water in 148(77.89%) raw milk samples, Detergent in 62(32.9%), Cane Sugar 41(21.8%), Caustic Soda 32(16.8%), Sodium Salts 31(16.4%), Starch 21(11.1%), Formalin 18(9.4%), Urea 15(8.05%), Foreign Fat 12(6.4%), Hydrogen Peroxide 04(2.3%), Glucose 02(1.3%), Boric Acid 02(1.1%) and sulfate salts 02(1.1%) in raw milk samples. Conclusions: The assessment of quality of fresh milk showed poor quality milk with the provision of different sort of adulterants in 77.89% raw milk samples and alarming sign of semi synthetic milk in 2.63% samples.